2018
DOI: 10.1111/1745-9125.12179
|View full text |Cite
|
Sign up to set email alerts
|

Body‐worn Cameras as a Potential Source of Depolicing: Testing for Camera‐induced Passivity

Abstract: Contentious debate is currently taking place regarding the extent to which public scrutiny of the police post-Ferguson has led to depolicing or to a decrease in proactive police work. Advocates of the "Ferguson effect" claim the decline in proactive policing increased violent crime and assaults on the police. Although police body-worn cameras (BWCs) are touted as a police reform that can generate numerous benefits, they also represent a form of internal and public surveillance on the police. The surveillance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 60 publications
(92 reference statements)
2
74
1
3
Order By: Relevance
“…Braga, Sousa, et al (2018) and Katz et al (2014), however, discovered that arrests increase for BWC-wearing officers compared with non-BWC officers, as does the Toronto Police Service (2016). Finally, neither Grossmith et al (2015) nor Wallace, White, Gaub, and Todak (2018) found any significant impact from BWCs on arrests stemming from violent crimes or calls for service, respectively. These mixed findings occur within both randomized controlled experiments as well as quasi-experimental research.…”
Section: Impact Of Bwcs On Arrest and Citation Behaviorsmentioning
confidence: 85%
See 1 more Smart Citation
“…Braga, Sousa, et al (2018) and Katz et al (2014), however, discovered that arrests increase for BWC-wearing officers compared with non-BWC officers, as does the Toronto Police Service (2016). Finally, neither Grossmith et al (2015) nor Wallace, White, Gaub, and Todak (2018) found any significant impact from BWCs on arrests stemming from violent crimes or calls for service, respectively. These mixed findings occur within both randomized controlled experiments as well as quasi-experimental research.…”
Section: Impact Of Bwcs On Arrest and Citation Behaviorsmentioning
confidence: 85%
“…Some of these activities are controversial (for example, the use of stop-question-and-frisk), whereas others involve fewer enforcement actions (for example, community engagement strategies). Wallace et al (2018) framed this discussion of the impact of BWCs on proactivity in terms of whether BWCs caused "de-policing" or "camera-induced passivity" of officers. Perhaps BWCs make officers more fearful of scrutiny, which leads them to "pull back" on engaging more proactively with the public.…”
Section: Impact Of Bwcs On Proactivitymentioning
confidence: 99%
“…A recent Spokane (WA) study found that, while officers in Spokane equipped with BWCs observed an 80% reduction in complaints, officers without BWCs also observed a 50% decrease. Then, once issued BWC's, complaints dropped by another 50% (White, Gaub, Janne, & Todak, 2018).…”
Section: Citizen Complaintsmentioning
confidence: 99%
“…As Wallace et al (2018) noted BWCs expose officers to increased scrutiny and risk of public and departmental scrutiny which may result in officers seeking ways to reduce those risks. In most cases, this reduction would come in the form of self-initiated or proactive policing such as drug interdiction or gang suppression rather than calls for service.…”
Section: Use Of Forcementioning
confidence: 99%
See 1 more Smart Citation